PEMBELAJARAN TEMATIK UNTUK MENYEIMBANGKAN KERJA OTAK KANAN DAN OTAK KIRI: matematika, otak kanan, otak kiri - Erlin Ladyawati (Universitas PGRI Adi Buana, 2011)
Thematic learning is a kind of learning activity. This model of learning combines several learning materials in one theme. The purpose of thematic learning is to give meaningful experience to students. Webbed thematic learning is a learning approach that has a certain theme. After developing one general theme into specific themes, the themes could be related to other field studies. It is believed that those themes could improve students' learning activity. Left-brain, closely related to IQ, is a rational brain. This brain has several characteristics. Those characteristics arelogical, • arithmetic, verbal, segmental, focus, linear, differential, and time¬dependable.Another brain, called right brain, is emotional brain that closely related toEQ. It also has several characteristics, such asintuitive, spatial, visual, holistic, diffuse, parallel (lateral), similar, and non time-dependable. Fact showsthat left-brain is used more frequently in school through lecture and course book.It brings the benefit for the students, which only have arithmetic and verbal ability in the left-brain. In other words, the students do not use all brain potencies. In fact, the students that have different ways of thinking could have different ways of learning. It is recommended that one school should have a learning method, which could accommodate the students two brains' work. It is possible for thematic learning to combine one theme in several learning activities. Those activities would help the students, the teachers, and the parents to know which part of brain the students use regularly. Further, the teachers and the parents are hoped to direct an effective education for their students. Effective education means the education, which is appropriate with the students' talent and interest. The purpose of this process is to describe the two brains' work in the webbed thematic learning of elementary students.